Exploring Street Vendors Characteristics and Social-Economic Significance in Mwanza Tanzania - Nasibu Rajabu (Journal of Business and Management Review, 2022)
The street vending business is an important employment opportunity in African cities. Millions of youths, less educated, women, and the poor make their living through selling on the street. Despite being important, little is known regarding their typologies, social-economic importance, and challenges hence difficult to design contextualized interventions for improving their economic wellbeing. This paper is exploring the nature, characteristics, and typologies of street vendors in Mwanza Tanzania. Data was collected from 396 respondents through qualitative and quantitative techniques. The findings show who are the street vendors, their importance in economic growth, and the challenges confronting their activities. From these findings, different interventions can be engineered to improve their businesses. The government and development stakeholders need to rethink the best approach of accommodating street vending and other informal activities to the formal economy. This is important because the number of street vendors is increasing every day due to a fall informal employment, rural street migration, and unattractive productivity in the agricultural sector.